Can blue mussel shells be used for retrospective 14C-analysis in the marine environment of nuclear power plants? - Bjarheim,Sofia (2024)
Carbon-14 (14C) is one of the most important contributors to the collective effective dose of the public due to radioactive releases from nuclear power plants. However, the discharge of 14C from nuclear power plants (NPPs) into water has not been measured previously. The aim of this project was to the develop a method for retrospectively analysing the annual discharge of dissolved inorganic 14C. As the shells of blue mussels (Mytilus Edulis) form annual structures they can be used to acquire information about approximately the past ten years. The method developed within this project identified the annual rings and extracted samples from the shells, which are known to be built up of inorganic carbon from the habitat of the mussel. The 14C content in the samples were analysed, and though the method still needs to be improved, the results were promising, and agree with previous studies on 14C along the Swedish west coast.
Keywords: Radionuclide; Marine Environment; Blue Mussels; 14C; Nuclear Power Plant